2012
DOI: 10.3390/ijms13010774
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Fungal Infections in Patients with Hematologic Malignancies (Aurora Project): Lights and Shadows During 18-Months Surveillance

Abstract: The aim of this multicenter prospective study was to evaluate the incidence of invasive fungal infections (IFIs) in adult and pediatric patients with hematologic malignancies, involving nine nosocomial facilities in Southern Italy over a period of 18 months. Furthermore, results of an environmental microbial surveillance routinely carried out in some of the enrolled hospitals are reported. A total of 589 onco-hematological patients were enrolled and 27 IFIs were documented. The main infections were caused by y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 27 publications
4
33
0
3
Order By: Relevance
“…These results are in accordance with those of two previous studies carried out in controlled environments of the same hospital, where an uncommon fungi contamination was found [34,35]. Our data do not confirm the findings from Verhoeff et al, which showed that active sampling was better at collecting fungal species [36] and from Asefa et al which found that the SAS air sampler showed higher numbers of fungi species and mean CFU/plate compared to settle plates [37].…”
Section: Resultssupporting
confidence: 93%
“…These results are in accordance with those of two previous studies carried out in controlled environments of the same hospital, where an uncommon fungi contamination was found [34,35]. Our data do not confirm the findings from Verhoeff et al, which showed that active sampling was better at collecting fungal species [36] and from Asefa et al which found that the SAS air sampler showed higher numbers of fungi species and mean CFU/plate compared to settle plates [37].…”
Section: Resultssupporting
confidence: 93%
“…This study is a subset of the AURORA Project [12, 13], a multicenter, observational study, performed between February 2007 and August 2008.…”
Section: Methodsmentioning
confidence: 99%
“…The majority of these infections occur in patients with haematological malignancies or other immunosuppressive conditions 1. The reason for this increase is multifactorial and includes impaired host defence, haematopoietic stem cell transplantation, ablative radiation therapy and use of immunosuppressive agents 2 .…”
Section: Discussionmentioning
confidence: 99%